Faktor-faktor yang berhubungan dengan kadar malondialdehyde plasma pada penyandang diabetes mellitus tipe 2 - Nazarina Nazarina; Reviana Christijani; Yunita Diana Sari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Diabetic is associated with the risk of having lipid peroxidation causing macro and micro vascular diseases. Malondialdehyde (MDA) is a mutagen product of lipid peroxidation.Objective: This research was to identify some factors associated to plasma MDA (P-MDA) level in type 2 diabetes mellitus.Method: Eighty two subjects were randomly recruited. Subjets were members of Persadia, physical training club for diabetic at Mardjoeki Mahdi Hospital in Bogor. Data of fruits, vegetables, and nuts-legumes-seeds consumption were collected by interviewing using semi quantitative food frequency questionnaires. Fasting blood glucose and plasma MDA were assayed using Wills method, based on the reaction of thiobarbituric acid. Other data such as physical training, smoking status, and diseases history were collected by interviewing using structured questionnaires. Nutritional status data was determined as body mass index. All data was analyzed using Odds Ratio (OR) and logistic regression test to identify the dominant factors contributed to P-MDA level.Results: Factors that contribute to P-MDA level is vegetables, nuts-legumes-seeds consumption and physical training. Consuming vegetables less than 300 g/d and nuts-legumes-seeds less than 2.5 servings/d are associated significantly with having high level of P-MDA (≥0.8 nmol/L), respectively OR=5 (95%CI:1.154-22.02) and OR=4.8 (95%CI:1.26-18.57). Not having physical activity routinely is risk for having high level P-MDA (OR=1.3; 95%CI:1.12-1.45). Those factors are associated to P-MDA level independently.Conclusion: Vegetables and nuts-legumes-seeds consumption have a significant contribution to P-MDA level, it is important to know further which type and chemical content in those food that can prevent lipid peroxidation.